Six-Month Outcomes for Collaborative Care Management of Depression Among Smoking and Nonsmoking Patients - Daniel R. Witt; Gregory M. Garrison; Cesar A. Gonzalez; Terrence J. Witt; Kurt B. Angstman (SAGE Publishing, 2017)
Background: Collaborative care management (CCM) is an evidence-based model that contributes to better outcomes for depression treatment in the primary care setting. Tobacco use increases overall economic costs, morbidity, and mortality and has been shown to impact behavioral health outcomes. Our study aims to observe clinical outcomes for depression treatment for patients with comorbid tobacco use and depression within the CCM model. Methods: A retrospective chart review study of 2826 adult patients with depression enrolled in CCM was performed to determine the association between regular tobacco use and depression outcomes. Baseline intake data consisting of clinical and demographic variables along with 6-month follow-up of Patient Health Questionnaire-9 (PHQ-9) scores for smokers (n = 727, 25.7%) and nonsmokers (n = 2099, 74.3%) were obtained. Depression remission was defined as a PHQ-9 score <5 and persistent depressive symptoms (PDS) as a PHQ-9 score ≥10 at 6 months. Results: Using an intention-to-treat analysis, the multivariate modeling demonstrated that smokers, at 6 months, had an increased adjusted odds ratio (AOR) for PDS: 1.624 (95% CI: 1.353-1.949). Furthermore, smokers had a lower AOR of depression remission: 0.603 (95% CI: 0.492-0.739). Patient adherence to treatment was also lower in smokers with an AOR of 0.666 (95% CI: 0.553-0.802). Conclusions: Smokers enrolled in CCM were associated with reduced treatment adherence and worse outcomes for depression treatment at 6 months compared to nonsmokers, even when baseline clinical and demographic variables were controlled. Thus, new tailored practices may be warranted within the CCM model to treat comorbid depression and tobacco use disorders.